ADVERSITY QUOTIENT ON MOSLEM ENTREPRENEURS IN ERA COVID-19 PANDEMIC - Rizki Al Gifari; Zaharuddin; Reza, Iredho Fani (Asosiasi Psikologi Islam (API) Himpsi, 2022)
This study aims to describe the adversity qoutient of entrepreneurs during the COVID-19 pandemic in Palembang. Method used in this research is a qualitative research method with a descriptive design. Subjects in this study amounted to 2 men who are owners / business owners in the city of Palembang. Furthermore, the data collection methods in this study used interviews, observation and documentation. Meanwhile, data analysis uses data collection, data reduction/data reduction, data display and conclusions/verification. Results of the research by the researchers that the two subjects never gave up and were able to get through the difficulties and obstacles that they run as entrepreneurs. The hardest thing you have to fight is lies in yourself, including don't give up easily, perseverance must always be carried out, ready to take risks, be patient and never give up. Because to be a successful entrepreneur you must be able to accept risks and be willing to get back up.